Urdu Afsany ki Tehqeeq o Tanqeed main Dr. Anwaar Ahmad ka hissa - Ali, Muhammad Said; Khurshid, Abid; Zahra, Shazma (sourcecoder, 2022)
Dr. Anwaar Ahmad’s research and criticism about Urdu short stories is by no mean insignificant. He increases his thesis of PhD about ’’ Urdu Afsana: Apny Siasi aur Smaji Tnazur main’’ in book form with the name of ’’Urdu Afsana: Aik Sdi ka Qissa’’. First of all he discusses 150 fiction’s writers. In third edition he discusses 245 fiction’s writers from 1903 to 2017 [almost above to one century].In this book, he has explained and divided fiction writers their behaviors, tendencies and movements inspite of chronologically. I explain in this essay the critical work of Dr. Anwaar Ahmad about Urdu short stories.